Peran Guru dalam Menstimulasi Kemampuan Membaca, Menulis dan Berhitung (Calistung) pada Anak di RA Mawaddah Palangka Raya - Ali Iskandar Zulkarnain; Saudah Saudah (Mathematics Education Study Program, 2025)
This research discusses the role of teachers in stimulating reading, writing and counting (calistung) skills in early childhood at RA Mawaddah Palangka Raya. Calistung skills are an important basis in children's education, which supports their readiness for the next level of education. This study uses a qualitative approach with observation and interview methods to analyze the role of teachers as mentors, facilitators, and classroom managers. The results showed that teachers at RA Mawaddah were able to create fun learning through a play while learning approach. Learning media such as pictures, letter blocks, and guidebooks are used to help children recognize letter sounds, write, draw, and count simply. Teachers also provide attention and emotional support so that children feel comfortable and motivated. The effective role of teachers not only helps children master calistung, but also encourages the development of their confidence and interest in learning. This research confirms the importance of teacher innovation and creativity in the calistung learning process to support optimal early childhood development.